Sport psychology in the physical culture sciences. A review - Paweł Piepiora; Agnieszka Rauk-Kubacka; Rafał Kubacki (Nicolaus Copernicus University in Toruń, Poland - University Sports Center, 2021)
Background and aim. The important role of sports psychology is often emphasized. But not everyone is aware that it applies to the entire area of physical culture. The aim of this article is to present the role of sports psychology and the positioning of this discipline in physical culture sciences. Matherial and method. The collected material consisted only of the works of sports psychologists available in Poland. The method of source materials analysis was used. Analysis with deductive reasoning and synthesis with inductive reasoning were used. Results. The importance of sport psychology for the sciences of physical culture and its theoretical and practical tasks are presented. Conclusions. Sport psychology is a discipline in the field of physical culture sciences. It deals with theoretical (research, education, diagnosis, analyzes, interventions, counseling) and practical (mental training) mechanisms and laws governing the psyche and human behavior in sport, physical education, tourism and recreation, rehabilitation and health training, using knowledge in the field of psychology and physical culture.